Mg/N double doping strategy to fabricate extremely high luminescent carbon dots for bioimaging - Li, Fan; Liu, Changjun; Yang, Jian; Wang, Zheng; Liu, Wenguang; Tian, Feng (RSC advances, 2014)
Carbon dots (CDs) with quantum yield up to 83% have been synthesized with a Mg/N double doping fluorescence-enhanced strategy. Besides N-mediated surface passivation by ethylenediamine, the Mg-citric acid chelate played the roles of introducing Mg and preserving the carboxyl group, both greatly contributing to the photoluminescence enhancement of the final CDs. Importantly, the N- and Mg-doping functioned in concert without mutual influence.